2014
DOI: 10.1007/s10493-014-9843-6
|View full text |Cite
|
Sign up to set email alerts
|

Acaricidal activity of ethanolic extract of Artemisia absinthium against Hyalomma anatolicum ticks

Abstract: The aim of the study was to evaluate the in vitro efficacy of different concentrations of ethanolic extract obtained from the aerial parts of Artemisia absinthium in comparison to amitraz on adults, eggs and larvae of Hyalomma anatolicum using the adult immersion test (AIT), egg hatchability test and larval packet test (LPT), respectively. Four concentrations of the extract (2.5, 5, 10 and 20%) with three replications for each concentration were used in all the bioassays. In AIT, the mortality rates at 2.5, 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Whereas, various alcoholic extracts (ethanolic and methanolic) of different parts for numerous plants, e.g. Acmella oleracea, Ageratum conyzoides, Aloe rupestris, Argemone mexicana, Artemisia absinthium, Berberis tinctoria, Caesalpinia gaumeri, Cissus quadrangularis, Clematis brachiata, Cleome gynandra, Dalbergia sissoo, Datura metel, D. stramonium, Dodonaea viscose, Eupatorium adenophorum, Euphorbia rothiana, Neoglaziovia variegata, Ficus sycomorus, Lobelia leschenaultiana, Monsonia angustifolia, Pelargonium luridium, Semecarpus anacardium, Solanum sisymbrifolium, Strobilanthes foliosus, Schkuhria pinnata, Sclerocarya birrea and Tabernaemontana elegans…..etc., recorded 10-100% efficiency against hard ticks within 24 hours to 14 days of treatment (Dantas et al, 2015;Ghosh et al, 2015a, b;Godara et al, 2015Godara et al, , 2018Banumathi et al, 2016;Cruz et al, 2016;Kumar et al, 2016;Muyobela et al, 2016;Singh et al, 2016;Anholeto et al, 2017;Rosado-Aguilar et al, 2017;Fouche et al, 2017Fouche et al, , 2019Vasconcelos et al, 2018;Figueiredo et al, 2019;Politi et al, 2019;Kemal et al, 2020;Upadhaya et al, 2020). Notably, the ticks killing activity of all extracts increases with increasing concentration and exposure time (Kemal et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…Whereas, various alcoholic extracts (ethanolic and methanolic) of different parts for numerous plants, e.g. Acmella oleracea, Ageratum conyzoides, Aloe rupestris, Argemone mexicana, Artemisia absinthium, Berberis tinctoria, Caesalpinia gaumeri, Cissus quadrangularis, Clematis brachiata, Cleome gynandra, Dalbergia sissoo, Datura metel, D. stramonium, Dodonaea viscose, Eupatorium adenophorum, Euphorbia rothiana, Neoglaziovia variegata, Ficus sycomorus, Lobelia leschenaultiana, Monsonia angustifolia, Pelargonium luridium, Semecarpus anacardium, Solanum sisymbrifolium, Strobilanthes foliosus, Schkuhria pinnata, Sclerocarya birrea and Tabernaemontana elegans…..etc., recorded 10-100% efficiency against hard ticks within 24 hours to 14 days of treatment (Dantas et al, 2015;Ghosh et al, 2015a, b;Godara et al, 2015Godara et al, , 2018Banumathi et al, 2016;Cruz et al, 2016;Kumar et al, 2016;Muyobela et al, 2016;Singh et al, 2016;Anholeto et al, 2017;Rosado-Aguilar et al, 2017;Fouche et al, 2017Fouche et al, , 2019Vasconcelos et al, 2018;Figueiredo et al, 2019;Politi et al, 2019;Kemal et al, 2020;Upadhaya et al, 2020). Notably, the ticks killing activity of all extracts increases with increasing concentration and exposure time (Kemal et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…The chloroform extract of the plant Artemisia absinthium had acaricidal properties on engorged females, eggs and unfed larvae of the tick R. sanguineus (Godara et al 2014). The ethanolic extract of the plant A. absinthium had acaricidal properties on adults, eggs and larvae of the tick Hyalomma anatolicum (Godara et al 2015). A repellent effect of a toluene extract of Artemisia abrotanum and essential oil of A. herba-alba against the nymphs of the tick Ixodes ricinus was occurred (Tunon et al 2006;El-Seedi et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…(Minjauw and Mc Leod, 2003), and therefore more exposed to acaricide, according to the t-test, the high mortality % of Hyalomma spp., was 31.25% compared to the lower mortality % of Boophilus spp., was 23.75%, but their difference was not significant. Godara, et al (2015) revealed that ethanolic extract obtained from the aerial parts of Artemisia absinthium has acaricidal properties and could be useful in controlling, adults, eggs and larvae of Hyalomma anatolicum.…”
Section: Discussionmentioning
confidence: 99%